HLA in isolated REM sleep behavior disorder and Lewy body dementia - Yu, Eric; Krohn, Lynne; Ruskey, Jennifer A; Asayesh, Farnaz; Spiegelman, Dan; Shah, Zalak; Chia, Ruth; Arnulf, Isabelle; Hu, Michele T M; Montplaisir, Jacques Y; Gagnon, Jean-François; Desautels, Alex; et al. (medRxiv, 2023)
BACKGROUND AND OBJECTIVES: Isolated/idiopathic REM sleep behavior disorder (iRBD) and Lewy body dementia (LBD) are synucleinopathies that have partial genetic overlap with Parkinson's disease (PD). Previous studies have shown that neuroinflammation plays a substantial role in these disorders. In PD, specific residues of the human leukocyte antigen ( HLA ) were suggested to be associated with a protective effect. This study examined whether the HLA locus plays a similar role in iRBD, LBD and PD. METHODS: We performed HLA imputation on iRBD genotyping data (1,072 patients and 9,505 controls) and LBD whole-genome sequencing (2,604 patients and 4,032 controls) using the multi-ethnic HLA reference panel v2 from the Michigan Imputation Server. Using logistic regression, we tested the association of HLA alleles, amino acids and haplotypes with disease susceptibility. We included age, sex and the top 10 principal components as covariates. We also performed an omnibus test to examine which HLA residue positions explain the most variance. RESULTS: In iRBD, HLA-DRB1 *11:01 was the only allele passing FDR correction (OR=1.57, 95% CI=1.27-1.93, p =2.70e-05). We also discovered associations between iRBD and HLA-DRB1 70D (OR=1.26, 95%CI=1.12-1.41, p =8.76e-05), 70Q (OR=0.81, 95% CI=0.72-0.91, p =3.65e-04) and 71R (OR=1.21, 95% CI=1.08-1.35, p =1.35e-03). In HLA-DRB1 , position 71 ( p omnibus =0.00102) and 70 ( p omnibus =0.00125) were associated with iRBD. We found no association in LBD. DISCUSSION: This study identified an association between HLA-DRB1 11:01 and iRBD, distinct from the previously reported association in PD. Therefore, the HLA locus may play different roles across synucleinopathies. Additional studies are required better to understand HLA's role in iRBD and LBD.